Biblical figures in deuterocanonical and cognate literature - Lichtenberger, Hermann 1943- (Berlin [u.a.] De Gruyter, 2009)
The present volume of the DCLY collects the contributions of the International Conference of the "International Society for the Study of Deuterocanonical and Cognate Literature" (ISDCL), held in Tübingen/Germany. The articles on the reception and function of Biblical figures in Deuterocanonical and other Early Jewish Literature are devoted to the question of how the meaning of individual biblical figures changed in Hellenistic times. In a variety of approaches, the religious function of these figures in a period of vast political and cultural changes is analyzed, as well as their role in the process of re-establishing Jewish identity in a time, in which the Jewish people suffered from harsh oppression and lived scattered throughout the world. The attempt to address the question of changing perceptions of Biblical figures as well theologically and historically is a first step on the way towards an integration of the topic in the larger framework of a systematic reviewing of post-Biblical theological developments.
Elia-Traditionen bei vor- bzw. frührabbinischen WundertäternAbraham unser Vater; Elija redivivus im Markus-Evangelium?; Biblical Figures in the Armenian Tradition; Backmatter
Includes bibliographical references and index
Electronic reproduction; Available via World Wide Web
Online-Ausg.
Keywords: Bible -- Criticism, interpretation, etc -- Congresses; Bible -- Biography -- Congresses; Apocryphal books (Old Testament) -- Criticism, interpretation, etc -- Congresses; Jewish religious literature -- History and criticism -- Congresses; Konferenzschrift